Review of diffuse cortical injury on diffusion-weighted imaging in acutely encephalopathic patients with an acronym: “CRUMPLED”() - Koksel, Yasemin (Eur J Radiol Open, 2018)
PURPOSE: Acute encephalopathic syndromes can present a diagnostic challenge due to the wide range of possible etiologies, which also can have vastly different outcomes. The presence of diffuse cortical injury (DCI) on diffusion-weighted imaging (DWI) can help narrow the differential diagnosis. The aim of this review is to categorize the range of possible etiologies of DCI into a useful acronym, "CRUMPLED". METHODS: A review of the PACS system was completed to find a characteristic example of patients with DCI on DWI from different etiologies. The diagnosis was confirmed for each example via a subsequent review of the electronic medical record used to assess for data such as biopsy results, laboratory values, and clinical correlation. The electronic exhibit intends to demonstrate several sample cases of each letter within the acronym, and to demonstrate which types of DCI are potentially reversible or irreversible. FINDINGS/DISCUSSION: The possible etiologies of DCI on DWI can be organized using the acronym "CRUMPLED": 'C' = Creutzfeldt-jakob disease, 'R' =  reversible cerebral vasoconstriction syndrome; 'U' = urea cycle disorders (hyperammonemia) and Uremia; 'M' = mitochondrial (cytopathy/encephalopathy); 'P' = prolonged seizure and posterior reversible encephalopathy (PRES); 'L' = laminar necrosis (hypoxic-ischemic encephalopathy) and liver disease (acute hepatic encephalopathy); 'E' = encephalitis (infectious meningoencephalitis); 'D' = diabetes mellitus (hypoglycemia). Other secondary imaging findings (outside of DWI) can be used to help differentiate between the aforementioned etiologies, such as the use of ADC maps, FLAIR imaging, intravenous contrast. CONCLUSION: "CRUMPLED" is proposed as a convenient acronym for the categorization of a diverse range of acute etiologies associated with DCI on DWI, arising from varying degrees of cytotoxic edema. These etiologies can range from being potentially reversible (e.g. hyperammonemia or prolonged seizures) to irreversible (e.g. hypoxic-ischemic injury).